Living with others: fostering radical cosmopolitanism through citizenship politics in Berlin. Issue 1 (1st January 2017) - Baban, Feyzi; Rygiel, Kim
ABSTRACT: A growing refugee and migration crisis has imploded on European shores, immobilizing E.U. countries and fuelling a rise in far-right parties. Against this backdrop, this paper investigates the question of how to foster pluralism and a cosmopolitan desire for living with others who are newcomers. It does so by investigating community-based, citizen-led initiatives that open communities to newcomers, such as refugees and migrants, and foster cultural pluralism in ways that transform understandings of who is a citizen and belongs to the community. This study focuses on initiatives which seek to build solidarity and social relations with newcomers, but in ways that challenge citizen/non-citizen binaries based on one of our field research sites: Berlin, Germany. The paper brings insights from critical citizenship studies, exploring how citizenship is constituted through everyday practices, into dialogue with radical cosmopolitanism, particularly through Derrida's works on 'unconditional hospitality'. This radical cosmopolitan literature theorizes possibilities for building relational ontologies between guest and host, citizen and newcomer, in ways that are not based on exclusion, but engagement with difference and which challenge antagonistic forms of self-other and citizen-non-citizen dichotomies. Illustrative examples based on community-led initiatives in Berlin demonstrate how this spirit of radical communitarianism is put into practice through everyday lived experience and demonstrate that it is possible to develop a cosmopolitan spirit through exchange and transformation of both the self and other by engaging with rather than seeking to eliminate difference in the aims of constituting a universal around which cosmopolitanism can be built.